Relationship of social media addiction with social interactions and feeling of empathy in nursing students - Hanik Endang Nihayati; Adelia Dwi Lailyvira Ramadhania; Lailatun Nimah (Link Journal of Mental Health, 2025)
Introduction: The rapid advancement of technology has develop it difficult for students to avoid the use of social media. While social media offers numerous advantages that support daily life, it also brings both positive and negative consequences. One of the negative impacts is a decline in social interaction and reduced empathy among users. Objective: This research intends to explore the association between social media addiction, social interaction, and empathy levels. Methods: This research employed a cross-sectional design. A total of 170 nursing students were selected through simple random sampling. The independent variable was social media addiction, while the dependent variables were social interaction and empathy. Data were gathered using questionnaires and analyzed with the Spearman rho test, applying a significance level of α < 0.05. The design in this study used cross-sectional. Result: The findings indicate a significant relationship between social media addiction and social interaction (p = 0.003), as well as between social media addiction and empathy (p = 0.019). Conclusion: The study concludes that excessive social media use can negatively influence social interactions and empathy. Other factors may also contribute to diminished social engagement and sensitivity. Further research is encouraged to identify additional causes behind the decline in social interactions and empathetic behavior.